Analyzing Human Capital Readiness and Organizational Digital Transformation Toward Industry 4.0 PT. Telekomunikasi Indonesia Witel Madiun - Ardanta, Wigakarim; Sushandoyo, Dedy (Journal of Business and Management, 2020)
Abstract. The purpose of this research is to find out how the readiness of human capital and digital transformation of the organization at Telkom Witel Madiun toward change in industry 4.0. The analysis technique used in this study is to analyze employee perceptions about the gap that occurs between the present condition and the expected conditions of each variable consisting of factors such as Knowledge, Hard Skill, Soft Skill, and Attitude using Importance Performance Analysis (IPA). Each variable in these factors will be mapped in the Cartesian diagram quadrant to find out which variable should be considered. The subjects of this study is Telkom Witel Madiun human capital, Telkom Witel Madiun full-time employees. Furthermore, researchers used qualitative through interviews to find out how Telkom Witel Madiun dealing with digital transformation. The results of this study will produce the condition of human capital at Telkom Witel Madiun and then will give the right suggestion or solution in accordance with the previous analysis. Although Telkom Witel Madiun already using a digitalization on their operational business, they need to improve their human capital due to the technology advancement nowadays to create more efficient and accurate work.Keywords: Industry 4.0, Human Capital, Gap Analysis, Generation, Digital Transformation